Impact of EML4‐ALK Variants and TP53 Status on the Efficacy of ALK Inhibitors in Patients With Non‐small Cell Lung Cancer - Zihua Zou; Lige Wu; Xuezhi Hao; Yan Li; Li Liang; Yangchun Gu; Jianming Ying; Junling Li; Puyuan Xing (Thoracic Cancer)
ABSTRACT Background The clinical implications of different EML4‐ALK fusion variants remain poorly elucidated in the era of second‐generation ALK inhibitors. Methods This was a retrospective cohort study, wherein patients diagnosed with locally advanced or metastatic non‐small cell lung cancer harboring EML4‐ALK fusion were stratified into two cohorts based on their first‐line treatment: Cohort 1 received alectinib, while Cohort 2 received crizotinib. Statistical analysis was employed to investigate the impact of different EML4‐ALK variants and TP53 status on the efficacy of first‐line ALK‐TKIs. Results Finally, 49 patients were enrolled in cohort 1 and 53 patients in cohort 2. In cohort 1, patients with long EML4‐ALK fusion variants exhibited prolonged PFS (NR vs. 34.0 m, p = 0.004, HR = 0.30, 95% CI: 0.12–0.74) and an elevated 5‐year OS rate (93.3% vs. 68.4%, p = 0.020, HR = 0.12, 95% CI: 0.02–0.62) compared to those with short variants. The median PFS was not reached in TP53‐wt group and 47.0 m in TP53‐mut group (p = 0.087, HR = 0.44, 95% CI: 0.17–1.17). The TP53‐wt group exhibited a superior 5‐year OS rate (100% vs. 77.8%, p = 0.030) compared to TP53‐mut group. In cohort 2, the median PFS was 14.0 m in long variant group and 12.9 m in short variant group (p = 0.094, HR = 0.65, 95% CI: 0.37–1.13); the median OS was not reached in long variant group and 69.2 m in short variant group (p = 0.254, HR:0.62, 95% CI: 0.27–1.42). However, the efficacy of first‐line crizotinib did not appear to be influenced by the TP53 status. Conclusions EML4‐ALK short variants and TP53 mutations are both adverse factors for first‐line alectinib efficacy, but they have little effect on first‐line crizotinib.